SYSTEMATIC REVIEW: ANAPLASTIC LARGE CELL LYMPHOMA FOLLOWING BREAST IMPLANT SURGERY - Kezia Eveline; Rizqi Shabrina Lestari; Beta Subakti Nata’admadja; Lavonia Berlina Adzalika (Jurnal Rekonstruksi dan Estetik)
Highlights: